______revolutions/min
Answer:
x = -2/3, 1/3
Step-by-step explanation:
Step 1: Factor
(3x + 2)(3x - 1) = 0
Step 2: Find roots
3x + 2 = 0
3x = -2
x = -2/3
3x - 1 = 0
3x = 1
x = 1/3
Answer:
Step-by-step explanation:
factor ; (3x-1)(3x+2)=0
then make both 3x-1 and 3x+2 equal to 0
(3x-1)=0 solve 3x+2=0
+ 1 +1 -2 -2
_______ _______
3x = 1 3x = -2
x =1/3 x= -2/3
check for to make sure both solutions work by plugging back into the equation
Let x be the number of needed years.
1. He deposits $10,000 into his checking account and he will withdraw $1,200 from his checking account each year. Then after x years he will have $10,000-$1,200x in his checking account.
2. He deposits $2,000 into his savings account and his savings account earns 8% interest each year, then after x years he will have
3. Equate these amounts of money:
4. Solve this equation:
Conclusion: he needs nearly 6.663 years.